Acute oral complications in a pediatric patient with acute lymphoid leukemia. Issue 6 (29th December 2015) - Kamasaki, Yoko; Satoh, Kyoko; Nishiguchi, Miyuki; Hoshino, Tomonori; Fujiwara, Taku
Abstract: Pseudomonas aeruginosa is a low‐virulence pathogen that can cause infection in immunocompromised patients. Among pediatric hematologists, it is known that careful attention should be paid to P. aeruginosa as the bacteria responsible for intraoral inflammation, and antibiotic therapy targeting P. aeruginosa is the first‐line treatment during neutropenia in patients with hematological malignancy. Immunosuppressed patients, however, are at high risk of developing inflammation. Here, we report a case involving a 10‐year‐old patient with acute lymphoid leukemia (ALL), in which P. aeruginosa synergistically acted with pre‐existing gingivitis to induce unusual oral necrotic lesions, leading to acute buccal cellulitis and pus discharge from external sinus tracts.